Public sector leadership in assessing and addressing risk - Young, Peter C.; Grima, Simon; Gonzi, Rebecca Dalli (Emerald studies in finance, insurance, and risk management, 2022)
Public Sector Leadership in Assessing and Addressing Risk explores risk management in practice, taking a specific focus on the identification of risks in the European public sector while contextualising its Eurocentric analysis within a global setting. The volume lays important groundwork for understanding the main philosophical premises of risk management. Navigating the text's philosophical underpinnings such as 'Risk Management is a misnomer', the editors provide deep insight into global, strategic, and operational risk management that will prove invaluable for any practitioner. Providing high quality academic research, ESFIRM provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale.